Faktor-Faktor yang Berhubungan dengan Status Gizi pada Anak Autis di Pusat Layanan Autis Banjarmasin Tahun 2014 - Nany Suryani; Magdalena Magdalena; Doni Aqbar; Poltekes Banjarbaru; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2015)
Autism is a disease characterized with the breakdown of communication, social and behavioral limitations and attention. Children with autism have limited food choices, because they should not be eating selected foods. According to the arrangements with the conditions of foods and nutrition security also nutritional status of children with autism are better able to correct the interference suffered by children with autism. This study aims to determine the factors related with nutritional status in children with autism in the autism service center Banjarmasin 2014. This study uses an analytical method with cross sectional design. This study was conducted on 37 children with autism and their mother respondents. The results of this study are the most autistism children aged 7-9 years as many as 14 respondents (37,83%). The most gender is male as many as 32 respondents (86,49%). The most mother's level of knowledge is good as many as 34 respondents (91,9%). Level of mother's education is the most widely being as many as 17 respondents (45,94%). The level of energy consumption is the most over as many as 16 respondents (43,2%). The level of protein intakes was excessive a total of 32 respondents (86,5%). Nutritional status of children with autism is the most normal as many as 17 respondents (45,94%). There is no relationship between the level of knowledge of the nutritional status of mother with autistic children. Based on the results of statistical tests show, the level of maternal knowledge gained p=0,596, the level of protein intake obtained p=0,133, which means there is no relationship between the level of mother's knowledge and level of protein intake and nutritional status. Mother's level of education obtained p=0,032, the level of energy consumption obtained p=0,000, which means there is a relationship between mother's education level and the level of energy consumption and nutritional status of children with autism.